2019
DOI: 10.1002/jcb.28731
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear stress bodies: Interaction of its components in oncogenic regulation

Abstract: Oncogenesis involves continuous genetic alterations that lead to compromised cellular integrity and immortal cell fate. The cells remain under excessive stress due to endo‐ and exogenous influences. Human Satellite III long noncoding RNA (SatIII lncRNA) is a key regulator of the global cellular stress response, although its function is poorly explained in cancers. The principal regulator of cancer meshwork is tumor protein p53, which if altered may result in chemoresistance. The heat shock factor 1 (HSF1) bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Our previous in silico study showed a strong SatIII RNA and p53 protein interaction (Figure 7a,b). The SatIII‐interacting residues present on p53 DNA binding domain appeared functionally significant in cellular stress and cancer, which, if altered, may lead to malignant cell fate (Chatterjee et al, 2019). Several research groups also have shown that p53 intrinsically interacts with specific lncRNAs in cancer (Chaudhary & Lal, 2017; Lin et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous in silico study showed a strong SatIII RNA and p53 protein interaction (Figure 7a,b). The SatIII‐interacting residues present on p53 DNA binding domain appeared functionally significant in cellular stress and cancer, which, if altered, may lead to malignant cell fate (Chatterjee et al, 2019). Several research groups also have shown that p53 intrinsically interacts with specific lncRNAs in cancer (Chaudhary & Lal, 2017; Lin et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…(a) Docked complex representing interactions between SatIII and p53 with interacting amino acid residues present on p53 DNA binding domain (yellow) (adapted from Chatterjee et al, 2019). (b) Molecular interaction analysis by PatchDock beta v1.3 shows interaction between mutp53 and SatIII leads to change in amino acid residues present on p53 DNA binding domain (pink) (adapted from Chatterjee et al, 2019). (c) In control condition (unaltered Sat III levels), p53 expression is low in HeLa cells (upper panel).…”
Section: Resultsmentioning
confidence: 99%
“…sat III transcripts are also perturbed in a variety of human cancer cell lines and similar to the involvement of hsrω in biogenesis of omega speckles and their aggregation during stress, the sat III transcripts also form nuclear stress bodies and act as a sink for various RNA processing and heat shock factors [18,33]. Indeed, several other studies [20, 62,63]…”
Section: Cell Autonomous Perturbations In Hsrω Affect Multiple Processes Linked To Tumor Progressionmentioning
confidence: 98%